â€œTHE INFLUENCE OF CUSTOMER VALUE, BRAND TRUST, AND EMOTIONAL RELATIONSHIP TOWARD CUSTOMER TAPLUS LOYALTYâ€ (Study on BNI Branch Of Undip Semarang) - Yuliani, Endah Wahyu; Suryoko, Sri; Dewi, Reni Shinta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
This research was motivated by the tendency of customers have accounts at several banks are often regarded as common practice in the banking industry in this country. This suggests that to boost customer loyalty is not an easy job. In particular, this study discusses the BNI which decreased loyalty index based on Indonesian Bank Loyalty Award 2014. The higher of the value that customer perceived, the customer loyalty will be higher too. In addition, trust and management of the relationship between banks and customers is important to encourage customers to have a bond with the product used.The objective of this research is to examine the influence of customer value, brand trust and emotional relationship toward customer Taplus BNI loyalty. The type of this research is explanatory research. Non-probability technique that is purposive sampling were used as sampling technique with sample amounted to 98 people. The data were analyzed using correlation coefficient, simple linear regression, multiple linear regression, determination coefficient, t and F test using SPSS 16.0.The result of data analysis showed that variable customer value (X1), brand trust (X2), and emotional relationship (X3) either partially or simultaneously have a positive influence on loyalty (Y). Customer value is a variable that gives the biggest influence while brand trust gives the smallest influence toward loyalty.The advice that given to BNI about customer value is socialization of e-banking have to more intense, adding cash deposit machine facilities and self-passbook printing machine, and more attractive promotion. About brand trust is disclosure provisions of promotional prizes, clarity standard complaint handling time and improving IT systems. About emotional relationship is improving personal inform about promotion and event, human resource development and improvement of the relationship between the bank and its customers.